Obligate autotrophy at the thermodynamic limit of life in a new acetogenic bacterium - Frolov, Evgenii N.; Elcheninov, Alexander G.; Gololobova, Alexandra V.; Toshchakov, Stepan V.; Novikov, Andrei A.; Lebedinsky, Alexander V.; Kublanov, Ilya V. (Frontiers in Microbiology, 2023)
One of the important current issues of bioenergetics is the establishment of the thermodynamic limits of life. There is still no final understanding of what is the minimum value of the energy yield of a reaction that is sufficient to be used by an organism (the so-called "biological quantum of energy"). A reasonable model for determination of the minimal energy yield would be microorganisms capable of living on low-energy substrates, such as acetogenic prokaryotes. The most prominent metabolic feature of acetogens is autotrophic growth with molecular hydrogen and carbon dioxide as the substrates, which is hardly competitive in environments. Most probably, that is why only facultative autotrophic acetogens have been known so far. Here, we describe the first obligately autotrophic acetogenic bacterium Aceticella autotrophica gen. nov., sp. nov., strain 3443-3AcT. Phylogenetically, the new genus falls into a monophyletic group of heterotrophic bacteria of the genera Thermoanaerobacterium, Thermoanaerobacter, and Caldanaerobacter (hereinafter referred to as TTC group), where the sole acetogenic representative has so far been the facultatively autotrophic Thermoanaerobacter kivui. A. autotrophica and T. kivui both are acetogens employing energy-converting hydrogenase (Ech-acetogens) that are likely to have inherited the acetogenesis capacity vertically from common ancestor. However, their acetogenic machineries have undergone different adjustments by gene replacements due to horizontal gene transfers from different donors. Obligate autotrophy of A. autotrophica is associated with the lack of many sugar transport systems and carbohydrate catabolism enzymes that are present in other TTC group representatives, including T. kivui.